I pentecostalismi del territorio romano Una ricerca etnografica - Russo, Carmelo (Studi e materiali di storia delle religioni, 2016)
In 2013 and 2014 we conducted a research about Pentecostal Movement in Rome. We found 106 churches and almost 10.000 believers. Lots of them are Italian people. Different continents are represented: Europe, South America, Asia and Africa. The biggest community is the Romanian group: it has 2.079 believers. There are many differences among the migrant groups. Migrant Pentecostalism is in a never-ending changing process, which has to accommodate to an unknown social context and produces new realities. Migrant Pentecostal communities are very important to social and cultural integration. It is true for churches in which Italian people and immigrants stay together and for "ethnic" churches too, especially at the beginning of migrant experience, because they function as social and identity protection. (English)